5b + 11 - 2b = 3b + 11
10a+7b undefined variables cannot be determined
5+3b? :3
ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.
We can combine the like terms. So the b2 can be combined with the 2b2 to give 3b2. Likewise the 3b plus the -5b gives -2b.Therefore, b2 + 3b - 5b + 2b2 = 3b2 - 2b.
-b+5b-2b=2b
5b + 11 - 2b = 3b + 11
It is an expression that can be simplified to: 3a-2b+c
8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3
10a+7b undefined variables cannot be determined
5b plus 5-3b-7 is 2b-2.
3a - 2b
5+3b? :3
b=7
ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.
5b - 3 - 2b = 6b - 3 3b - 3 = 6b - 3 3b - 6b = 3 - 3 b = 0
We can combine the like terms. So the b2 can be combined with the 2b2 to give 3b2. Likewise the 3b plus the -5b gives -2b.Therefore, b2 + 3b - 5b + 2b2 = 3b2 - 2b.